Structural insights into the role of architectural proteins in DNA looping deduced from computer simulations. (21st March 2013) - Olson, Wilma K.; Grosner, Michael A.; Czapla, Luke; Swigon, David
Abstract : Bacterial gene expression is regulated by DNA elements that often lie far apart along the genomic sequence, but come close together during genetic processing. The intervening residues form loops, which are organized by the binding of various proteins. For example, the Escherichia coli Lac repressor protein binds DNA operators, separated by 92 or 401 bp, and suppresses the formation of gene products involved in the metabolism of lactose. The system also includes several highly abundant architectural proteins, such as the histone-like (heat-unstable) HU protein, which severely deform the double helix upon binding. In order to gain a better understanding of how the naturally stiff DNA double helix forms the short loops detected in vivo, we have developed new computational methods to study the effects of various non-specific binding proteins on the three-dimensional configurational properties of DNA sequences. The present article surveys the approach that we use to generate ensembles of spatially constrained protein-decorated DNA structures (minicircles and Lac repressor-mediated loops) and presents some of the insights gained from the correspondence between computation and experiment about the potential contributions of architectural and regulatory proteins to DNA looping and gene expression.